Management accounting practices among Bumiputera manufacturing small and medium enterprises / Erlane K Ghani, Muhamad Fadhil Jaafar and Maz Ainy Abdul Azis - Ghani, Erlane K; Jaafar, Muhamad Fadhil; Abdul Azis, Maz Ainy (Faculty of Accountancy, 2019)
The purpose of this study is to examine the practises of Management Accounting Practises (MAPs) among the Bumiputra Small and Medium Companies (SMEs) in furniture manufacturing sector. Five management accounting practices specifically focused on costing system, budgeting system, performance evaluation system, decision support system and strategic management system. The respondents for the study are the Bumiputra Small and Medium companies that have registered with Malaysia Timber Industry Board (MTIB) as at December 2017. The data was analysed by using descriptive and bivariate analysis. Findings have shown that there was some negative perception among Bumiputra SMEs in using the MAPs with their firm financial performance. Therefore, there is a need for more exposing application of MAPS through training and couching for Bumiputra SMEs in order to increase their knowledge in MEPS and used its’ as one of the strategic management tools to increase their competitive advantages in furniture industry market local and internationally.